Implementing Blended Learning Across an Entire Curriculum to Enhance Student Engagement. - Philips, John Arul (2016)
In Asia, diverse and changing demographics fit well with the 'no one size fits all'of blended learning where flexibility and the ability in corporate all forms of learning is crucial in facilitating the productive co-existence and development of a multi-generational student body and workforce.This session will highlight key areas to focus on when implementing a blended learning curriculum.